A rare case report of panuveitis with retinochoroidal involvement, retinitis, and retinal vasculitis due to extensive tinea corporis - Konana, Vinaya Kumar; Babu, Kalpana (Frontiers in Ophthalmology, 2023)
A 40-year-old asian Indian lady, diagnosed to have idiopathic panuveitis(elsewhere) since 3 years and on oral steroids 20mg/day and methotrexate 25mg/week, presented to us with worsening of vision in both eyes. Her BCVA was perception of light in right eye and counting fingers close to face in left eye. Slit lamp examination showed an AC reaction (1+) in both eyes with posterior synechia and total cataract in right eye and pseudophakia in left eye. Left fundus showed vitritis, vitreous membranes, chorioretinitis, multifocal areas of retinitis and retinal vascular sheathing. Systemic examination showed extensive multifocal areas of tinea corporis infections in the hands and torso. Due to the leukocytosis (22,000 cells/mm3), diagnostic vitrectomy was initially deferred and oral itraconazole 100mg twice a day was given for 3 months. The vitritis got a little better and her total WBC improved with treatment of the skin infection. Following a diagnostic vitrectomy later in left eye, resolving areas of retinitis were seen. Complete resolution of eye inflammation was seen at the end of 6 weeks. At 6 months follow-up, her BCVA was 6/18(OS) and she was off oral steroids and methotrexate, with no recurrence of inflammation. We speculate a probable association between the ocular inflammation and extensive tinea corporis infection based on the therapeutic response to itraconazole.